Diseño de un sistema de riego por goteo para el cultivo de café (Coffea arabica) en el barrio Guarango, parroquia Santa Teresita, cantón Espíndola, provincia de Loja - Moreno Cruz, Jandry Fernando (2023)
Due to the little irrigation technology in the place, the design of a drip irrigation system was carried out for the growing coffee (Coffee arabica) in an area of 5,019.76 m2, in order to contribute to efficient management. of soil and water resources, and propose a solution to the low technification of plot irrigation. The description of two profiles was carried out and later the analysis of the soil through the collection of samples for the determination of CC, PMP, Da and texture, likewise the agronomic and hydraulic design of the irrigation system was carried out, in the agricultural property of the del barrio Guarango, parroquia Santa Teresita, cantón Espíndola, provincia de Loja. In the agronomic design, the irrigation needs of the coffee grow were determined with a value of 5.42 mm day-1. The selected area was divided into 2 irrigation subunits 2 600 m2 and 2 500 m2, which demand a flow of 2.4l s-1. From the results of the analysis of the physical properties of the soil, the irrigation sheet of 13.13 mm day-1 was determined with an irrigation frequency of 3 days and an irrigation time of 98 minutes in subunit 1 and irrigation sheet of 21 ,14 mm day-1, frequency of 4 days and irrigation time of 158 minutes in subunit 2. Concerning the hydraulic design, in the irrigation subunits the main and secondary network with a nominal diameter of 50 mm of 1.25 MPa and, the laterals of 16 mm of 0.40 MPa with self-compensated drippers of 4l h-1. In the analysis of the water used for irrigation, which comes from the quebrada del Desmonte, the following results were obtained: salinity of 0.13 dS m-1, pH 7, sodium absorption ratio (SAR) 1.53 mg l-1, carbonate of residual sodium (CSR) <1.25 meq l-1 and total dissolved solids of 80 mg l-1. The installation of 5 019.76 m-1 of drip irrigation has a cost of $.2969. The development of this research will allow efficient use of soil and water resources to improve the productivity of coffee growing in the area. Keywords: Drip irrigation, agronomic and hydraulic design, water quality.